TOOTHBRUSHING AND CARDIOVASCULAR HEALTH: A NARRATIVE REVIEW OF POPULATION-BASED EVIDENCE - Galaz-Parrao, Loreto (2025)
Emerging evidence from population-based studies increasingly underscores a significant association between oral hygiene practices—specifically toothbrushing frequency—and cardiovascular health outcomes. This brief narrative review synthesizes epidemiologic and mechanistic data, demonstrating that infrequent toothbrushing is consistently linked to elevated risks of stroke, coronary artery disease, and heart failure. These associations appear partially mediated by systemic inflammation (e.g., hsCRP, IL-6), metabolic dysregulation (e.g., HbA1c), and transient bacteremia. Numerous large-scale studies and meta-analyses report that brushing twice or more daily is associated with significantly reduced cardiovascular risk. Importantly, these findings converge despite differences in study populations, methodologies, and endpoints. The evidence supports regular toothbrushing as a feasible, low-cost, and globally scalable intervention with measurable systemic benefits. Integration of oral hygiene promotion into public health frameworks may contribute meaningfully to cardiovascular disease prevention, particularly in underserved communities.